Linking Susceptibility to Infectious Diseases to Immune System Abnormalities among HIV-Exposed Uninfected Infants - Ruck, Candice; Reikie, Brian A.; Marchant, Arnaud; Kollmann, Tobias R.; Kakkar, Fatima (Frontiers in Immunology, 2016)
HIV-exposed uninfected (HEU) infants experience increased overall mortality from infectious causes when compared to HIV-unexposed uninfected (HU) infants. This is the case in both the resource-rich and resource-limited settings. Here, we explore the concept that specific types of infectious diseases that are more common among HEU infants could provide clues as to the potential underlying immunological abnormalities. The most commonly reported infections in HEU vs. HU infants are caused by encapsulated bacteria, suggesting the existence of a less effective humoral (antibody, complement) immune response. Decreased transplacental transfer of protective maternal antibodies has consistently been observed among HEU newborns, suggesting that this may indeed be one of the key drivers of their susceptibility to infections with encapsulated bacteria. Reassuringly, HEU humoral response to vaccination appears to be well conserved. While there appears to be an increase in overall incidence of acute viral infections, no specific pattern of acute viral infections has emerged; and although there is evidence of increased chronic viral infection from perinatal transmission of hepatitis C and cytomegalovirus, no data exist to suggest an increase in adverse outcomes. Thus, no firm conclusions about antiviral effector mechanisms can be drawn. However, the most unusual of reported infections among the HEU have been opportunistic infections, suggesting the possibility of underlying defects in CD4 helper T cells and overall immune regulatory function. This may relate to the observation that the immunological profile of HEUs indicates a more activated T cell profile as well as a more inflammatory innate immune response. However, both of these observations appear transient, marked in early infancy, but no longer evident later in life. The causes of these early-life changes in immune profiles are likely multifactorial and may be related to in utero exposure to HIV, but also to increased environmental exposure to pathogens from sicker household contacts, in utero and postnatal antiretroviral drug exposure, and, in certain circumstances, differences in mode of feeding. The relative importance of each of these factors will be important to delineate in an attempt to identify those HEU at highest risk of adverse outcomes for targeted interventions.